2006
DOI: 10.5694/j.1326-5377.2006.tb00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in diagnosing colorectal cancers in patients presenting with abdominal distension

Abstract: Objective: To determine the usefulness of abdominal ultrasonography for diagnosing colorectal cancer in patients presenting with abdominal distension. Design, setting and participants: A prospective case series of consecutive adult patients with abdominal distension admitted to the National Taiwan University Hospital between January 2001 and July 2004. All participants were examined by abdominal ultrasonography. Those with suspected colorectal tumours on ultrasonography had follow‐up colonoscopy, while all oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
1
0
1
Order By: Relevance
“…The results are consistent with those of Chen et al [14] who found that ultrasonography was 92.8% sensitive, 98.8% specific, 94.7 percent positive predictive, and 98.0 percent negative predictive.…”
Section: Discussionsupporting
confidence: 92%
“…The results are consistent with those of Chen et al [14] who found that ultrasonography was 92.8% sensitive, 98.8% specific, 94.7 percent positive predictive, and 98.0 percent negative predictive.…”
Section: Discussionsupporting
confidence: 92%
“…W nomenklaturze angloamerykańskiej określany jako "target-sign" lub "pseudo-kidney-sign". Obraz raka jelita grubego w ultrasonografii to ubogoechowe pogrubienie ściany jelita z bogatoechowym centrum [3,4]. Guzy stromalne z reguły są hipoechogeniczne w badaniu ultrasonograficznym [5].…”
Section: Omówienieunclassified
“…The incidence of colon cancer is increased in people aged 40‐50, and the ratio is 2 to 3:1 for male: female . In the middle and late stage, patients are always with characters of abdominal distension, indigestion, abdominal pain, mucus or sticky stool . Companying with tumour ulceration, blood loss and toxin absorption, patients show more serious symptoms, including anaemia, hypothermia, fatigue, weight loss and lower extremity oedema .…”
Section: Introductionmentioning
confidence: 99%